2023
DOI: 10.21203/rs.3.rs-3057132/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plant growth promoting endophytic fungi of the wild halophytic rice Oryza coarctata

Abstract: Background Plant growth-promoting endophytic fungi (PGPEF) associated with halophytes have the potential to boost plant growth and salinity tolerance in crops enabling cultivation in the coastal lands. Methods Endophytic fungi from the wild halophytic rice Oryza coarctata were isolated, characterized, identified and studied for their effects on plant growth and yield both with and with without salt stress. Key results: In this study, three different fungal endophytes were isolated from the halophytic wild r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…Interestingly, the difference in 1000-grain weight between paired and unpaired was significant without salt, which indicates the positive impact of pairing but not enough to show differences in the yield under salt stress. The positive impact of the pairing with Oc may be due to the plant growth promoting bacteria (Sarker et al, 2023) and endophytic fungus associated with Oc (Airin et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the difference in 1000-grain weight between paired and unpaired was significant without salt, which indicates the positive impact of pairing but not enough to show differences in the yield under salt stress. The positive impact of the pairing with Oc may be due to the plant growth promoting bacteria (Sarker et al, 2023) and endophytic fungus associated with Oc (Airin et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Any possible mutualism between Oc and Os may be inclusive of any endophytic microbes growing within the halophyte and helping to defend the commercial but sensitive genotype against the stress. Our earlier work has identified a highly significant plant growth promoting endophytic fungus associated with Oc roots and rhizomes (Airin et al, 2023). Apart from that, previous studies showed plants communicate with neighboring plants and modify their physiological and morphological features, including alterations in root system architecture (RSA) (Zhang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%